Corporate governance and tax strategies in Chinese listed firms - Ying, Tingting (2015)
Tax represents a significant cost to shareholders as well as to the firm, and it is generally expected tax aggressiveness are preferred. However, this argument ignores potential non-tax costs that could be associated with tax aggressiveness, especially those arising from agency problems and asymmetric information. This study aims to investigate the influence of corporate governance on taxaggressiveness of listed Chinese firms by adopting an agency perspective of the firm based upon the nexus of institutional arrangements in place in China. An innovation of this study is making use of available income tax reconciliation data to examine the determinants and effects of tax planning activities conducted by Chinese listed firms. We hand-collected a sample of 229 publicly-listed firms over the 2006-2012 period (1080 firm-year observations). This study advances a new, refined method of separating company book-tax differences (BTDs) into a 'normal' component of BTDs that arises as a result of divergence between Chinese GAAP and tax rules, and an 'abnormal' BTD component which is presumed to arise a result of earning management and tax planning. When using the refined decomposition of tax liability to examine the effects of corporate governance variables, we find that firms with political connectionsthrough controlling shareholder and through the state ownership are more tax aggressive than other firms. Our results suggest that political connectionsare a significant determinant of abnormal book-tax differences and their impacts should be accounted for in ‘relationship-based’ economies. In addition, incentive compensation appears to be another significant determinant of tax aggressiveness. In particular, we find that increase in managerial cash compensation tend to reduce the level of tax aggressiveness in a manner consistent with the optimal contracting view, which contribute to our overall understanding of the role of incentive compensation that plays in motivating managers' efforts.The empirical findings have direct policy implications for shareholders and tax administration in controlling and monitoring firms’ tax planning activities.